Nurturing families: One year pilot outcomes for a modified Parent Child Assistance Program in Australia. - Martyn Symons; Amy Finlay-Jones; Jennifer Meehan; Natalie Raymond; Rochelle Watkins (Public Library of Science (PLoS), 2022)
Alcohol and Other Drug (AOD) exposure during pregnancy is linked to serious adverse child outcomes, including Fetal Alcohol Spectrum Disorder (FASD). The Parent-Child Assistance Program (PCAP) supports women with problematic AOD use, who are pregnant or have young children, and are not effectively engaging with services. PCAP has been shown to reduce alcohol exposed pregnancies, promote AOD abstinence, increase employment and family planning and improve child outcomes. This manuscript reports the first pilot evaluation of the PCAP program delivered in Australia. A pre-post-intervention repeated measures design was used. Eleven women receiving PCAP from a not-for-profit organisation were invited to take part in the study, with eight providing complete pre-post data. Home visitation case management was provided by trained and experienced case-managers. Clients were assisted to engage with existing services effectively to meet their own goals via a combination of relational theory, motivational interviewing and harm reduction concepts. The PCAP Modified Addiction Severity Index 5th Edition was adapted for use in Australia and was used to measure domains of addiction severity related problems as the primary outcome. Secondary outcomes included client satisfaction and program fidelity. There were significant changes in composite addiction severity scores from baseline to one year. 80% of participants had periods of abstinence of longer than four months. All clients had better connection to services, no subsequent AOD exposed pregnancies, and were highly satisfied with the program. Four had children returned to their care. Implementation was similar to the original PCAP program with major differences including case-managers relying on training manuals only without undertaking in-person training; being more experienced; providing more direct AOD counselling; and having less supervision. The findings will inform future program delivery and methodology for a larger longitudinal study assessing outcomes at program exit.